Acute Development of Traumatic Intracranial Aneurysms After Civilian Gunshot Wounds to the Head - Serra, Riccardo; Wilhelmy, Bradley; Chen, Chixiang; Oliver, Jeffrey D; Stokum, Jesse A; Bodanapally, Uttam K; Simard, J Marc; Schwartzbauer, Gary; Aarabi, Bizhan (Journal of neurotrauma, 2024)
In previous studies, the incidence of traumatic intracranial aneurysms (TICAs) after civilian gunshot wound to the head (cGSWH) was ∼3%. Given the use of delayed vessel imaging, we hypothesize that a significant fraction of TICAs is missed on initial non-contrasted scans. This study was designed to characterize acute TICAs using admission computed tomographic angiography (aCTA) in cGSWH. Over the period from 2017 to 2022, 341 patients were admitted to R. Adams Cowley Shock Trauma Center with cGSWH; 136 subjects had aCTA ∼3 (standard deviation [SD] 3.5) h post-injury. Demographics, clinical findings, imaging techniques, endovascular/surgical interventions, and outcomes were analyzed. Mean age was 34.7 (SD 13.1), male:female ratio was 120:16. Average admission Glasgow Coma Scale (GCS) score was 6 (SD 3.9). Entry site was frontal in 41, temporal in 55, parietal in 18, occipital in 6, suboccipital in 9, temporo-parietal in 1, and frontobasal-temporal in 6. Projectiles crossed multiple dural compartments in 76 (55%) patients. 35 TICAs were diagnosed in 28 subject: 24 were located along the middle cerebral artery (MCA), 6 in the anterior cerebral artery (ACA), 3 in the internal carotid artery (ICA), 1 in the posterior cerebral artery (PCA), and 1 in the middle meningeal artery (MMA). Eleven TICAs resolved spontaneously in nine patients. Eight aneurysms were treated by endovascular means, two via combined endovascular/open approaches. Forty-nine patients died, 10 of whom had 15 TICAs. Eighty patients developed intracerebral hematoma s (ICHs). Regression models showed that the presence of an ICH was the main predictor of TICA in cGSWH. Larger ICHs (average 22.3 cc vs. 9.4 cc in patients with and without aneurysms, respectively) in patients with cGSWH suggest hidden TICAs. Nearly 30% of patients had spontaneous resolution within 1 week. When CTA was performed acutely, TICAs were 10 times more frequent in cGSWH than in previous literature, and those patients were more likely to proceed to surgery. Almost one third of patients in this series died from the devastating effects of cGSWH.